Musical and textual analyses of lullabies and folktales of Dusun Labuk at Eastern Sabah, Malaysia - Ang, Susan Ngar Jiu (2011)
This thesis describes the musical culture of the Dusun Labuk community in the Telupid District, Sandakan Division, Sabah State of Malaysia with special reference to the lullabies mongindong and the folktales tangon. Built upon existing literature of Dusun Labuk’s culture, this study contributes by giving a detailed musical description of the vocal traditions. The description of the Dusun Labuk’s culture includes the belief, worldview, lifestyle and musical practice in the most recent past and at present. Meanwhile, the Dusun Labuk’s folksongs, especially mongindong and tangon, are described in terms of song texts, musical structures and performance styles. From the fieldwork conducted, eight mongindong and 16 tangon are examined in this study. The textual analysis of mongindong focuses on the aspects of messages, expressions and placement of keywords while the textual analysis of tangon is carried out under the aspects of story characters, cultural elements and expressions. The textual materials of the folksongs reveal the Dusun Labuk’s belief, ideas, thoughts, values and views. Meanwhile, the tonal aspects of folksongs display the Dusun Labuk’s interpretation of their performance style of each genre and the concept of tonal arrangement in singing. The tonal structure of both genres can be understood as combination of melodic versions and their implied patterns of common melodic movements, which at the same time follow the traits of several melodic axes. The commonly observed melodic versions reveal the effect of exchange and sharing of musical ideas among the villagers while the unique versions indicate individual creativity. Based on the findings of analysis, a few issues are discussed which include genre identity, tonal arrangement and cultural expression. Through this, the creativity and cultural identity in music of the Dusun Labuk is informed. Further studies can focus on vocal traditions in other areas in Sabah State and may test the applicability of the analysis method used in this study.